Improved Lung Cancer Prevention Knowledge Among Older Adults Through Structured Health Education - Ni Wayan Prema Revina Sutami; I Wayan Mustika; Ketut Sudiantara; Agus Sri Lestari; I Wayan Suardana; Suparji Suparji (Health Dynamics, 2026)
Background: Lung cancer remains a major global public health problem and is one of the leading causes of cancer-related mortality, particularly among the elderly who are more vulnerable due to age-related physiological decline and prolonged exposure to risk factors such as smoking and environmental pollutants. Despite ongoing preventive efforts, limited knowledge and awareness regarding lung cancer prevention among older adults continue to hinder effective control strategies. This study aimed to determine the effect of booklet-based health education on the level of knowledge regarding lung cancer prevention among the elderly. Methods: This study employed a quantitative pre-experimental design using a one-group pretest–posttest approach. The study was conducted in the working area of UPTD Puskesmas I East Denpasar, Bali, Indonesia. The sample consisted of 103 elderly individuals selected through purposive sampling. Primary data were collected using a structured questionnaire measuring knowledge levels, while secondary data included respondent characteristics. Data were analyzed using descriptive statistics and the Wilcoxon signed-rank test. Results: The results showed that prior to the intervention, the majority of respondents had poor knowledge (59.2%), which decreased to 9.7% after the intervention. Conversely, the proportion of respondents with good knowledge increased from 11.7% to 47.6%. The mean knowledge score also increased from 49.26 to 74.39, with a statistically significant difference (p = 0.001). Conclusions: In conclusion, booklet-based health education was associated with a significant improvement in knowledge regarding lung cancer prevention among the elderly. This intervention can be considered a practical and effective strategy for enhancing health literacy in community settings.